Oceans [electronic resource] : a scientific history of oceans and marine life - Allaby, Michael (Discovering the Earth, 2009)
Discusses the history of various topics related to oceans and oceanography, covering mapping, the origins of ocean basics, the ocean floor, measurement of depth and flow, the creatures that inhabits the depths of the sea, and the adventures of modern explorers